Diuretic versus placebo in normotensive acute pulmonary embolism with right ventricular enlargement and injury: a double-blind randomised placebo controlled study. Protocol of the DiPER study. Issue 5 (22nd May 2015) - Gallet, Romain; Meyer, Guy; Ternacle, Julien; Biendel, Caroline; Brunet, Anne; Meneveau, Nicolas; Rosario, Roger; Couturaud, Francis; Sebbane, Mustapha; Lamblin, Nicolas; Bouvaist, Helene; Coste, Pierre; et al.
Abstract : Introduction: In acute pulmonary embolism (PE), poor outcome is usually related to right ventricular (RV) failure due to the increase in RV afterload. Treatment of PE with RV failure without shock is controversial and usually relies on fluid expansion to increase RV preload. However, several studies suggest that fluid expansion may worsen acute RV failure by increasing RV dilation and ischaemia, and increase left ventricular compression by RV dilation. By reducing RV enlargement, diuretic treatment may break this vicious circle and provide early improvement in normotensive patients referred for acute PE with RV failure. Methods and analysis: The Di uretic versus placebo in P ulmonary E mbolism with R ight ventricular enlargement trial (DiPER) is a prospective, multicentre, randomised (1:1), double-blind, placebo controlled study assessing the superiority of furosemide as compared with placebo in normotensive patients with confirmed acute PE and RV dilation (diagnosed on echocardiography or CT of the chest) and positive brain natriuretic peptide result. The primary end point will be a combined clinical criterion derived from simplified Pulmonary Embolism Severity Index (PESI) score and evaluated at 24 h. It will include: (1) urine output >0.5 mL/kg/min for the past 24 h; (2) heart rate <110 bpm; (3) systolic blood pressure >100 mm Hg and (4) arterial oxyhaemoglobin level >90%. Thirty-day major cardiac events defined as death, cardiac arrest, mechanical ventilation, need for catecholamine and thrombolysis, will be evaluated as a secondary end point. Assuming an increase of 30% in the primary end point with furosemide and a β risk of 10%, 270 patients will be required. Ethics and dissemination: Ethical approval was received from the ethical committee of Ile de France (2014-001090-14). The findings of the trial will be disseminated through peer-reviewed journals, and national and international conference presentations. Trial registration number: NCT02268903.